Global Warming Towards Human Health: A Literature Review - Schillaci Valley Mucci; Bafirman; Hendri Neldi; Donal Syafrianto; Dally Rahman; Fiky Zarya (Jurnal Penelitian Pendidikan IPA, 2023)
Global warming is a phenomenon of an increase in the average temperature of the earth's surface due to an increase in the concentration of greenhouse gases in the atmosphere, which not only affects the global ecosystem and climate, but also has a significant impact on human health. These impacts include an increase in heat-related diseases, the spread of infectious diseases, a decrease in air quality, and changes in disease patterns due to climate change. This study aims to identify and analyze the impact of global warming on human health through literature review from various sources such as journal articles, research reports, and health organization documents. The results showed that global warming increases the risk of heat stroke and dehydration, especially in vulnerable groups such as children and the elderly, as well as affecting the geographical distribution of disease vectors such as mosquitoes that can spread malaria and dengue fever. Rising temperatures also worsen air quality by increasing the concentration of surface ozone and airborne particles, which has an impact on the increase in respiratory diseases, as well as changing the seasonal and geographical patterns of diseases, including impacts on people's food security and nutrition. The conclusions of this study underscore the importance of coordinated mitigation and adaptation actions to reduce the health impacts of global warming, including policies to reduce greenhouse gas emissions, improve health systems, and educate the public on preventive measures, with the need for further research for effective and specific adaptation strategies for different affected regions and populations.